Conceptual approaches to the study of mechanisms and factors the destructive influence of social networks on the emotional sphere of the personality (Actual Problems of Psychology in Educational Institutions, 2023)
Factors of influence of social networks on the emotionalsphere of the personality are summarized: development of informationand communication technologies; low level of critical thinking; activeuse of manipulatives technologies (NLP tools, infection, persuasion, selfpromotion); uncontrolled presence in social networks, enhanced by extendeddistance learning. A list of factors that increase the destructive influenceis given: fabrication, distortion of facts, lies, fakes, clickbait, manipulativesemantics and rhetoric; sensationalism of events. The results of a surveyon the emotional direction of users by social networks are presented, thepurpose of the stay, the content of the materials that are used.
Keywords: influencing factors; manipulation; emotional orientation; information and communication technologies, social networks